Rising prevalence of subthreshold and major depressive symptom in South Korea: A trend analysis from 2014 and 2018 - Djoko Priyono; Sanghee Kim (PLoS ONE, 2025)
Introduction Subthreshold depression and major depressive symptoms are prevalent mental health conditions that significantly impact quality of life and contribute to South Korea’s high suicide rate. Despite their importance, few studies have examined temporal changes in the occurrence of these disorders in the Korean population. Objective This study aimed to estimate the prevalence of subthreshold depression and MDD using a large, representative sample of the South Korean population and analyze trends over time. Methods Data were obtained from 10,848 participants aged 19 and above in the Korean National Health and Nutrition Examination Survey (KNHNES) in 2014 and 2018. Depression severity was categorized using cutoff scores of 5-14 for subthreshold symptoms and ≥ 15 for severe symptoms. Results The prevalence of subthreshold depression increased from 12.90% in 2014 to 15.20% in 2018, while MDD rose from 4.7% to 7.0% (p < 0.001). Logistic regression analysis revealed that MDD (OR = 8.1, 95% CI = 2.34-11.23), college education (OR = 7.9, 95% CI = 4.23-10.00), and age above 65 years (OR = 8.1, 95% CI = 2.58-12.58) exhibited similar risks for suicide attempts. Conclusion Since 2014, there has been a sharp and sustained increase in both subthreshold and severe depressive symptoms among the Korean population. This alarming trend underscores the critical need for targeted prevention and intervention strategies.